A transcultural study of hoarding disorder: Insights from the United Kingdom, Spain, Japan, and Brazil. (April 2018) - Nordsletten, Ashley E.; Fernández de la Cruz, Lorena; Aluco, Elena; Alonso, Pino; López-Solà, Clara; Menchón, José M.; Nakao, Tomohiro; Kuwano, Masumi; Yamada, Satoshi; Fontenelle, Leonardo F.; Campos-Lima, André Luís; Mataix-Cols, David
Though problematic hoarding is believed to be a universal human behavior, investigations of clinically-defined hoarding disorder (HD) have been confined almost exclusively to Western countries. The current investigation sought to describe and directly compare the features of individuals meeting diagnostic criteria for HD across four distinct cultural settings. Participants were 82 individuals meeting DSM-5 diagnostic criteria for HD, recruited and assessed by trained clinicians at one of four project sites: London, Barcelona, Fukuoka, and Rio de Janeiro. A series of semi-structured interviews and self-report scales were administered, including assessments of socio-demographic characteristics, psychiatric comorbidity, and severity of hoarding and related features. Results indicate that the severity and core features of HD, as well as the cognitions and behaviors commonly associated with this condition, are largely stable across cultures. However, some differences in patient demographics—in particular age, marital status, and clinical expression—as well as comorbid psychiatric features also emerged. These findings confirm that HD, as defined in DSM-5, exists and presents with similar phenomenology across the studied cultures. Future, more fine-grained, research will be needed to study the features of the disorder in additional cultures (e.g., non-industrialized nations) and to evaluate the impact of these cultural aspects on the design of interventions for the disorder.